Dietary Patterns and Their Associations With the FTO and FGF21 Gene Variants Among Emirati Adults - Naja, Farah; Itani, Leila; Hammoudeh, Sarah; Manzoor, Shaista; Abbas, Nada; Radwan, Hadia; Saber-Ayad, Maha (Frontiers in Nutrition, 2021)
Purpose: To examine the dietary patterns and their associations with the FTO and FGF21 gene variants among Emirati adults. Methods: Using a cross-sectional design, healthy adult male and female Emiratis (n = 194) were recruited from primary health care centers in Sharjah, UAE. Participants completed a 61-item semi-quantitative food frequency questionnaire. In addition, a saliva sample was obtained for the genetic analysis. Genotyping was performed for FTOrs9939609(A>T), FTOrs9930506(A>G), FGF21 rs838133 (A > G), and FGF21 rs838145 (A > G). Dietary patterns were derived using the principal component analysis. Logistic regression analyses were used to examine the association of dietary patterns with genetic variants. Results: Three dietary patterns were identified: “Western”: consisting of fast food, sweets, and processed meat; “Traditional Emirati” rich in vegetables, traditional Emirati-mixed-dishes and whole dairy; while whole grains, low-fat dairy, and bulgur were components of the “Prudent” pattern. Subjects carrying the A allele of the FTO rs9939609 were 2.41 times more likely to adhere to the Western pattern compared to subjects with genotype TT (OR:2.41; 95%CI:1.05–5.50). Compared with subjects with A/A, those carrying the G allele of the FTO rs9930506 were more likely to follow a Western diet (OR: 2.19; 95%CI: 1.00–4.97). Participants carrying the risk allele (A) of the FGF21 rs838133 were twice more likely to adhere to the Traditional pattern as compared to subjects with genotype GG (OR: 1.9, 95%CI: 1.01–3.57). Conclusions: The findings of this study suggested associations among specific FTO and FGF21 gene variants with dietary patterns among Emirati adults. These findings could be used to inform evidence-based targeted nutrition preventive recommendations, especially those aiming to limit intake of western type foods.